LIQUIDITY MANAGEMENT AND FINANCIAL PERFORMANCE OF LISTED DEPOSIT MONEY BANKS IN NIGERIA - Bashiru Iliyasu Danmulki; Eniola Samuel Agbi; Lateef O. Mustapha (Gusau Journal of Accounting and Finance, 2022)
The study investigates the effect of liquidity management on financial performance of listed deposit money banks in Nigeria. Liquidity management was measured and proxy with capital adequacy ratio, liquidity ratio and loan to deposit ratio, however financial performance was proxy with Tobin’s Q. Secondary data source was utilized and it was extracted via the audited published annual reports and accounts of the banks selected covering the period from 2010-2019. Panel multiple regression technique was adopted as the technique of data analysis, while Stata 13 was used as the tool for analysis of data. Robustness tests which include heteroscedasticity, multicollinearity and normality test of standard error were conducted. Findings revealed that capital adequacy ratio have positive and significant effect on financial performance of listed deposit money banks in Nigeria. Liquidity ratio has significant but negative effect on financial performance of banks in Nigeria which connotes that high level of liquidity ratio will lead to low level of performance strategically for banks. Loan to deposit ratio has positive but insignificant effect on financial performance. It is therefore recommended that management of board should pursue increased capital with the Central Bank of Nigeria and the CBN should also make sure that banks met and continually meet the requirements in respect of capital adequacy before giving the license to operate. The management of the banks should ensure that most idle cash are investment into short term portfolios to attract higher returns which will eventually increase the value of the banks.